Pathogenicity of Root-knot nematode (Meloidogyne incognita) and Determination Threshold Level in Potato (Solanum tuberosum L.) crop cv. Lady Rosseta - Patel, Bhumika; Patel, D. B.; Tapre, Poonam V.; Singh, N. K.; Patel, Rushikesh (International Journal of Bio-resource and Stress Management, 2020)
Pot studies were undertaken to prove the pathogenicity of root-knot nematode (Meloidogyne incognita) and to determine the threshold level in potato cv. Lady Rosseta arranged with inoculum levels viz., 0 (uninoculated check), 10 (J2 plant-1 pot-1), 100 (J2 plant-1 pot-1), 1,000 (J2 plant-1 pot-1) and 10,000 (J2 plant-1 pot-1). Sixty days after inoculation, recorded data revealed that initial inoculum level of 100 Juveniles/plant/pot (10 kg soil) significantly reduced the plant growth parameters viz., plant height (cm), tuber weight (g), fresh shoot and root weight (g) and dry shoot and root weight (g) and were pathogenic to potato cv. Lady Rosseta. No significant reduction in plant growth parameters was observed between uninoculated check and initial inoculum level of 10 (J2 plant-1 pot-1). Maximum reduction in plant growth parameters were observed at inoculum level of 10,000 J2 plant-1 pot-1. Plant growth parameters in uninoculated check was higher than other treatments. Increase in root-knot index and number of root galls plant root1 (1 g) were noticed with increase in inoculum levels. Reproduction of root-knot nematode (M. incognita) in potato cv. Lady Rosseta revealed significant increase in nematode population parameters viz., different stages of embedded females and egg masses plant root1 (1 g), soil nematode population pot1 and total nematode population build-up with increase in inoculum level. Minimum nematode population parameters were recorded at inoculum level of 10 J2 plant-1 pot-1 and maximum nematode population parameters were recorded at inoculum level of 10,000 J2 plant-1 pot-1. Reproduction rate (Pf/Pi) decreased with increase in inoculum levels. It was maximum (404.90) at the inoculum level of 10 J2 plant-1 pot-1 and minimum (4.03) at the inoculum level of 10,000 J2 plant-1 pot-1.